(untitled) (Revista científica Olimpia, 2025)
This article analyzes the historical transformation in the management of rheumatoid arthritis (RA), from the harmful paradigm of immobilization to the consolidation of physical exercise as an essential adjuvant therapy. Its objective is to demonstrate how the synergistic integration of advanced pharmacological treatments and structured physical activity redefines the current standard of care. During the 20th century, absolute rest during inflammatory flares generated severe iatrogenic effects: muscle atrophy, accelerated osteoporosis, and irreversible functional disability. This approach began to reverse at the beginning of the 21st century, when robust studies showed that supervised and adapted exercise was not only safe but essential to counteract the systemic damage of inactivity. In parallel, the pharmacological revolution with biological agents and JAK inhibitors and the "treat to target" (T2T) strategy enabled effective inflammatory control, facilitating the viability of exercise. Recent research confirms key multisystem benefits: improved muscle strength and functional capacity (HAQ), bone protection against glucocorticoids, reduction of cardiovascular risk the main cause of mortality in RA and management of refractory symptoms such as fatigue and persistent pain. International guidelines (EULAR 2023, ACR 2021) thus endorse exercise as an essential non-pharmacological pillar of therapy. Therapeutic synergy is essential: drugs control underlying inflammation, while exercise restores physical function, prevents comorbidities, and optimizes quality of life. This strategic complementarity represents a paradigm shift in the comprehensive approach to RA, where therapeutic movement far from being an adjunct is an active component that enhances clinical outcomes and empowers patients.